In Silico Structural Protein Evaluation of the Phenylalanine Hydroxylase p.(Tyr77His) Variant Associated with Benign Hyperphenylalaninemia as Identified through Mexican Newborn Screening - Marcela Vela-Amieva; Miguel Angel Alcántara-Ortigoza; Ariadna González-del Angel; Isabel Ibarra-González; Liliana Fernández-Hernández; Sara Guillén-López; Lizbeth López-Mejía; Cynthia Fernández-Lainez (MDPI AG, 2023)
Hyperphenylalaninemia (HPA), which includes phenylketonuria (PKU), is a genetic autosomal recessive disorder arising from a deficiency in the enzyme named phenylalanine hydroxylase (PAH). Affected patients can experience severe and irreversible neurological impairments when phenylalanine (Phe) blood concentration exceeds 360 μmol/L (6 mg/dL). Here, we describe a female HPA patient who was born in Mexico to Cuban non-consanguineous parents and identified by newborn screening, and who bears the previously unreported PAH NM_000277.3(PAH):c.[229T>C];[1222C>T] or p.[Tyr77His];[Arg408Trp] genotype. At diagnosis, the patient showed a Phe blood level of 321 μmol/L (5.3 mg/dL), indicative of mild HPA. Neither of the PAH variants found in this patient had been previously reported in the mutational PAH spectrum of the Mexican population. The c.229T>C or p.(Tyr77His) PAH variant was previously related to mild HPA in the Swedish population. Our in silico structural analysis and molecular docking showed that mutated His 77 residue is located in the allosteric site of PAH at the interface of the two monomers. The PDBsum in silico tool predicted that this variant would cause minimal structural disturbance of the protein interface in the presence of Phe at the allosteric site. Docking studies revealed that these structural changes might be attenuated by the allosteric effect of Phe. Given the classic PKU phenotype conditioned by the "Celtic" or c.[1222C>T] or p.(Arg408Trp) PAH variant, which is the second variant in this patient, we propose that p.(Tyr77His) has a hypomorphic feature that could explain her mild HPA phenotype. Our results show the importance of following up on cases detected by NBS and the value of genetic studies and in silico tools that aid in the establishment of correct therapeutic strategies.